Evaluation of the Composition of the Cholesterol, Tocopherols, β-Carotene and Fatty Acids Profile of the Liver Tissue of Male Water Buffaloes (Bubalus bubalis) Managed in Different Ecosystems of the Eastern Amazon - Rodrigues, Laurena Silva (2023)
The diet offered to animals has a great influence on the composition of tissues and, consequently, the quality. The objective of this study was to evaluate the influence of Amazonian ecosystems, in the dry and rainy periods of the year, on the composition of cholesterol, tocopherols, -carotene and the fatty acid profile of the livers of water buffaloes (Bubalus bubalis) reared in the Eastern Amazon, in an extensive or intensive system. Total lipid content was influenced by the location and time of year (p < 0.05). Ninety-six male water buffaloes were used (12 per sampling period), aged between 24 and 36 months, with average weights of 432 kg (end of the rainy season) and 409 kg (end of the dry season). Total cholesterol, -tocopherol and -tocopherol influenced the relationship between extensive vs intensive ecosystems, location, periods and the interaction between the location and period of the year (p < 0.05). Animals raised in a pasture ecosystem had the highest values of omega-3, and those raised in confinement, the highest values of omega-6 (p < 0.05). The proportions of n-6/n-3 and hypocholesterolemia (7.14) and hypercholesterolemia (3.08%) (h/H) were found in greater amounts in animals raised in confinement (p < 0.05). The atherogenic index (AI) had a higher value in the rainy season, in animals raised in Santarém (2.37%), with no difference between pasture and feedlot ecosystems, except in animals raised in the rainy season in Nova Timboteua, with a lower AI (1.53%). The thrombogenicity index (TI) was higher in the livers of confined animals (0.32%) and lower (0.18%) in those raised in Nova Timboteua (rainy season). Amazonian ecosystems influence the nutritional values of buffalo liver, with the best nutritional values in animals in the extensive system.